2021
DOI: 10.1039/d1ra02310a
|View full text |Cite
|
Sign up to set email alerts
|

γ-Ray irradiation-induced unprecedent optical, frictional and electrostatic performances on CVD-prepared monolayer WSe2

Abstract: Our work showed a new defect inducing technique to engineer the bandgap and control the optical, frictional and electrostatic properties of atomically thin WSe2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Felix et al reported changes in the magnetic phase from diamagnetic to ferromagnetic and enhancement in the p-type doping in monolayer WS 2 after 400 Gy irradiation . Wu et al irradiated a monolayer WSe 2 film with a γ radiation dose ranging from 20 to 100 kGy, which resulted in n-type doping along with an enhanced electron-carrier concentration . Hence, the creation of defects by γ-rays can also be visualized as a positive application for achieving doping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Felix et al reported changes in the magnetic phase from diamagnetic to ferromagnetic and enhancement in the p-type doping in monolayer WS 2 after 400 Gy irradiation . Wu et al irradiated a monolayer WSe 2 film with a γ radiation dose ranging from 20 to 100 kGy, which resulted in n-type doping along with an enhanced electron-carrier concentration . Hence, the creation of defects by γ-rays can also be visualized as a positive application for achieving doping.…”
Section: Introductionmentioning
confidence: 99%
“…16 Wu et al irradiated a monolayer WSe 2 film with a γ radiation dose ranging from 20 to 100 kGy, which resulted in n-type doping along with an enhanced electron-carrier concentration. 17 Hence, the creation of defects by γ-rays can also be visualized as a positive application for achieving doping.…”
Section: Introductionmentioning
confidence: 99%